Crystal field splitting on D↔S transitions of atomic - Byrne, O.; Collier, M.A.; Ryan, M.C.; McCaffrey, J.G. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2010)
Narrow excitation features present on the [Ar]3d64s1 a6D(J = 9/2 – 1/2) ← [Ar]3d54s2 a6S1/2 transitions of manganese atoms isolated in solid Kr are analyzed within the framework of weak crystal field splitting. Use of the Wp optical lineshape function allowed identification of multiple zero-phonon lines for individual spin-orbit J states of the a6D ← a6S transition recorded with laser-induced excitation spectroscopy. Excellent agreement exists between the predicted crystal field splitting patterns for the J levels of the a6D state isolated in the «red» tetravacancy site of solid Kr. The tetrahedral crystal field of the «red» trapping site splits J > 3/2 levels of the a6DJ and a4D7/2 states by approximately 30 cm–1. This report represents the first definitive evidence of crystal field splitting, induced by the weak van der Waals interactions between a neutral metal atom and the rare gas atoms surrounding it in a well defined solid state site.